Molecular Prerequisites for Neutrophil Extracellular Trap Formation and Evasion Mechanisms of Staphylococcus aureus - von Köckritz-Blickwede, Maren; Winstel, Volker (Frontiers in Immunology, 2022)
NETosis is a multi-facetted cellular process that promotes the formation of neutrophil extracellular traps (NETs). NETs as web-like structures consist of DNA fibers armed with granular proteins, histones, and microbicidal peptides, thereby exhibiting pathogen-immobilizing and antimicrobial attributes that maximize innate immune defenses against invading microbes. However, clinically relevant pathogens often tolerate entrapment and even take advantage of the remnants of NETs to cause persistent infections in mammalian hosts. Here, we briefly summarize how Staphylococcus aureus, a high-priority pathogen and causative agent of fatal diseases in humans as well as animals, catalyzes and concurrently exploits NETs during pathogenesis and recurrent infections. Specifically, we focus on toxigenic and immunomodulatory effector molecules produced by staphylococci that prime NET formation, and further highlight the molecular and underlying principles of suicidal NETosis compared to vital NET-formation by viable neutrophils in response to these stimuli. We also discuss the inflammatory potential of NET-controlled microenvironments, as excessive expulsion of NETs from activated neutrophils provokes local tissue injury and may therefore amplify staphylococcal disease severity in hospitalized or chronically ill patients. Combined with an overview of adaptation and counteracting strategies evolved by S. aureus to impede NET-mediated killing, these insights may stimulate biomedical research activities to uncover novel aspects of NET biology at the host-microbe interface.